Single-Atom Catalysts on C3N4: Minimizing Single Atom Pt Loading for Maximized Photocatalytic Hydrogen Production Efficiency - Lazaar, Nawres; Wu, Siming; Qin, Shanshan; Hamrouni, Abdessalem; Bikash Sarma, Bidyut; Doronkin, Dimitry E.; Denisov, Nikita; Lachheb, Hinda; Schmuki, Patrik (Angewandte Chemie International Edition, 2025)
The use of metal single atoms (SAs) as co-catalysts on semiconductors has emerged as a promising technology to enhance their photocatalytic hydrogen production performance. In this study, we describe the deposition of very low amounts of Pt SAs (<0.1 at %) on exfoliated graphitic carbon nitride (C3N4) by a direct Pt−deposition approach from highly dilute chloroplatinic acid precursors. We find that − using this technique−a remarkably low loading of highly dispersed Pt SAs (0.03 wt %) on C3N4 is sufficient to achieve a drastic decrease in the overall charge transfer resistance and a maximized photocatalytic efficiency. The resulting low-loaded Pt SAs/C3N4 provides a H2 production rate of 1.66 m mol/h/mg Pt, with a remarkable stability against agglomeration; even during prolonged photocatalytic reactions no sign of light-induced Pt agglomerations can be observed. We ascribe the high performance and stability to the site-selective, stable coordination of Pt within the C3N4 structure. Notably the H2 production rate of the low-loaded Pt SAs surpasses the activity of Pt SAs deposited by other techniques or nanoparticles at comparable or even higher loading – the optimized Pt SAs decorated C3N4 show ≈5.9 times higher rate than Pt NP decorated C3N4.
CRIS-Team Scopus Importer:2025-01-31
Keywords: C; dark deposition; H; photocatalysis; Pt single atoms